To Shine Bright Like a Diamond: How Botswana Overcame The Resource Curse and its Implications on Population Health - Pettersson,Gemma (2024)
Botswana is known as the ‘Diamond of Africa’ due to its unique success in avoiding the resource curse, the paradox where resource-rich developing countries experience poor economic and social outcomes while trapped in a cycle of underdevelopment. Despite the consequences of the resource curse, such as higher corruption and conflict, impacting development as a whole, much of the existing literature defines the success of avoiding the resource curse through predominantly economic indicators. This has led to a gap in the literature regarding the social indicators of success. This thesis has a two-pronged aim; to explore the key factors that influenced Botswana’s success through a systematic literature of the discourse, and to bridge the literature gap by including positive health outcomes in the discussion - namely to use life expectancy at birth as an indicator of success, too. By emphasizing a more interdisciplinary approach, this study provides a more nuanced understanding of what shapes and indicates development in resource-rich countries, and opens the door for wider discussion on the resource curse without the bias of a solely economic viewpoint.
Keywords: The resource curse; Postcolonialism; Colonial legacies; Botswana; Life expectancy